A Potential Pathogenic SRD5A2 Mutation and rs632148, rs523349 and rs522638 Polymorphisms in Increasing the Risk of Syndromic Hypospadias in Indonesian Population - Rizki Diposarosa; Yunisa Pamela; Herry Herman; Yunia Sribudiani (The Indonesian Biomedical Journal, 2024)
BACKGROUND: Hypospadias, a congenital birth defect in male, is the opening of the urethra located on the ventral side of the penis. Several mutations in SRD5A2 encoding steroid 5 alpha-reductase type 2 protein have been identified in hypospadias and polymorphisms in this gene have been known to be associated with an increased risk of hypospadias. In this study, several crucial molecular analyses of the SRD5A2 gene and the association of the identified variants to the risk of syndromic hypospadias in Indonesian population were conducted.METHODS: Thirty-two isolated and 29 syndromic hypospadias patients were enrolled in this study. DNA was isolated from whole blood for the amplification of all exons and exon-intron boundaries of SRD5A2 by polymerase chain reaction (PCR), followed by Sanger sequencing. In silico analysis was performed using PolyPhen-2, Sorting Intolerant from Tolerant (SIFT) and Align GVGD. Statistical analysis was performed using Chi-squared test.RESULTS: A novel missense mutation c.32T>C/p.Leu11Pro was identified in one isolated hypospadias patient and the in silico analysis predicted the mutation to be pathogenic. Three polymorphisms were identified, two in the non-coding region (c.-62G>C/rs632148 and c.281+15T>C/rs522638) and one in exon-1 (c.265C>G/p.Val89Leu/rs523349). Mutant alleles of these polymorphisms were significantly associated with syndromic hypospadias with odds ratios (OR) of 3.4, 3.13 and 2.54 respectively.CONCLUSION: This study suggests that SRD5A2 mutation is one of the causes of hypospadias in Indonesian population and rs632148, rs523349 and rs522638 polymorphisms are significantly associated with an increased risk of syndromic hypospadias.KEYWORDS: mutation, polymorphism, SRD5A2, syndromic hypospadias